Influence of ionizing radiation on the stochasticity of overvoltage protection at low, medium, and high voltage levels in gas surge arresters - Jusić Alija R.; Lazarević Đorđe R.; Turković Irfan M. (Nuclear Technology and Radiation Protection, 2023)
The paper considers the possibility of improving the technical characteristics of gas surge arresters for the co-ordination of insulation at low voltage, medium voltage and high voltage levels. The idea for improving the characteristics of a gas surge arrester is based on the application of the radioactive source 241Am in the area of the surge arrester cathode. Intensive ionization with alpha particles significantly increases the number of free electrons in the space between electrodes, which shortens the time of their transition to initial electrons. This changes the Paschen curve of the gas surge arrester, narrows and flattens its impulse characteristic and reduces the stochasticity of the response of the gas surge arrester. All this results in a significant improvement in the characteristics of the gas surge arrester at all voltage levels. This improvement is particularly noticeable in the case of low voltage surge arresters. The paper is basically theoretical-experimental research. The experiments were performed under well-controlled laboratory conditions. The combined measurement uncertainty of all measurements was acceptable.